Refractory antiphospholipid antibody syndrome–induced thrombocytopaenia successfully treated with belimumab. (April 2022) - Yoshizuka, Riku; Hasegawa, Hisanori; Kamiya, Mari; Umezawa, Natsuka; Yasuda, Shinsuke
Antiphospholipid antibody syndrome (APS) is an autoimmune disease with clinical symptoms such as recurrent arterial/venous thrombosis, pregnancy morbidities and thrombocytopaenia. Antiphospholipid antibodies are suggested to be involved in the pathological condition of APS. Therefore, belimumab (BLM), which reduces autoantibody production from B cells, is expected to be effective in the treatment of APS. We report a case of a 63-years-old woman with APS with refractory thrombocytopaenia. Her thrombocytopaenia did not respond to antithrombotic therapy and immunosuppressive treatment including corticosteroids and rituximab but improved with BLM. This is the first report of an APS-induced thrombocytopaenia treated successfully with BLM. BLM should be an effective treatment for APS-related thrombocytopaenia.